2020
DOI: 10.1016/j.clml.2019.09.599
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for Rural Lymphoma Survivors: A Qualitative Study

Abstract: A qualitative study of lymphoma survivors living in rural Georgia was conducted using 12 individual semistructured telephone interviews. The travel distance was the greatest barrier to care, with other issues including communication and navigating between local clinics and larger cancer centers. The participants saw technology as an important solution and detailed their research priorities. Background: We gathered rural patient perspectives on lymphoma care and unmet needs throughout the treatment course to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 59 publications
(72 reference statements)
1
21
0
Order By: Relevance
“…Despite the limitations in making comparisons across qualitative studies, our findings from two previous studies involving predominantly White patients recruited in the same healthcare environment as the current study are distinct from the findings presented in this population. In the aforementioned studies, White patients expressed broad awareness of available clinical trials and commonly described the emotional impact that their lymphoma diagnosis had on them [34,35]. Several participants in our study stated that their illness did not affect them emotionally at all.…”
Section: Providing Social Support For Black Patientsmentioning
confidence: 71%
See 1 more Smart Citation
“…Despite the limitations in making comparisons across qualitative studies, our findings from two previous studies involving predominantly White patients recruited in the same healthcare environment as the current study are distinct from the findings presented in this population. In the aforementioned studies, White patients expressed broad awareness of available clinical trials and commonly described the emotional impact that their lymphoma diagnosis had on them [34,35]. Several participants in our study stated that their illness did not affect them emotionally at all.…”
Section: Providing Social Support For Black Patientsmentioning
confidence: 71%
“…The semi-structured interview guide was based on previous research in lymphoma populations [17,34,35], literature review, and the expertise of the researchers. Topics discussed included research experience, treatment plans, experiences with their clinical care team, and areas the participants felt researchers need to prioritize.…”
Section: Methodsmentioning
confidence: 99%
“…Our ndings were similar to a recent study conducted among rural Georgia cancer patients. Findings indicated that respondents had not participated in research often, usually due to a lack of access to research opportunities (Chen et al, 2020). However, this study focused on priorities from an individual perspective where ours focused on involvement of individuals from an organization-based standpoint.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a recent review of National Cancer Institute–designated cancer center websites showed that only 8 centers provided vaccine-related content to patients and caregivers through that platform [ 33 ]. Additionally, systems that alert and remind the many providers that care for cancer patients (primary care, oncology, surgeons, radiation oncologists, etc) about offering the vaccine may be lacking [ 34 ]. Ensuring that state-level vaccine registries are functional, capable to interphase between states, and are easily accessible to health care providers would also facilitate coordinating efforts between providers.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been proposed and tested to increase influenza vaccination rates in the general population including home visits, incentives/subsidies, implementation of standing orders, vaccine screening protocols, and reminders to patients and providers [ 34 , 36 , 37 ]. Implementing some of these strategies, particularly reminder systems to patients and providers, are predicted to result in vaccination rates exceeding 80% with a modest increase in cost [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%